Head Injuries in Contact Sports – Literature Review - Kacper Hoksa; Aleksandra Broda; Krzysztof Jodłowski; Ewa Dubniewicz; Paula Majewska; Alicja Staszek; Wiktoria Łoskot; Mateusz Matczak; Jan Szwech; Karol Jasiński (Quality in Sport)
Head injuries in athletes are an increasingly common issue, not only in professional sports but also due to the growing number of amateurs participating in contact sports. These sports include not only martial arts such as boxing, judo, or MMA but also team sports, including some of the most popular ones like soccer, rugby, American football, and hockey.